ABCs of Diversifying Information Resources among Rice Smallholders of Ghana. Issue 3 (26th May 2016) - Misiko, M.; Halm, E.
Abstract : Purpose: We investigated how information resource diversification can enhance smallholder agricultural knowledge in Ghana. Design/Methodology/Approach: Study tools and methods were questionnaire survey (N = 200), focus group discussion (N = 1), in-depth interviews (N = 18) and field direct observation. Findings: This study shows there existed diversity of information resources in Hohoe. This diversity was, however, devoid of a broad integration process to enhance smallholder access to and use of agricultural information. We demonstrate that new information channels or sources cannot function independently, but rather through an integrated approach that relies on a human facet of extension. Practical Implications: We illustrate the need for integrated extension that includes interactive field modules such as basic cell phone decision guides that support smallholder construction of solutions for their circumstances. This process requires new sets of smallholder skills and holistic extension schemes that diversify information resources through incorporation and adaptation, rather than substitution. New information resources can only be gradually mainstreamed through integration with more familiar extension means. They need a human interface because smallholder householders did not require same types and/or amounts of information. Human interface is essential to ensure critical groups including women access and utilise agricultural information resources, but without entrenching unfair task allocations among smallholder householders. Originality/Value: This paper illustrates how extension can be strengthened through new approaches. However, new approaches such as use of basic cell phones cannot be standalone processes; they require a human interface and an integrated process. The article presents actual data collected from the Ghana.